2020
DOI: 10.3389/fpsyt.2020.00856
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Profile and Correlates of Employment in People With Schizophrenia: The Role of Avolition

Abstract: Objective: Employment was associated with recovery in individuals with schizophrenia. Our study aimed to delineate the vocational profile and investigate factors associated with likelihood of employment in individuals with schizophrenia. Materials and Methods: 276 community dwelling outpatients with schizophrenia were recruited; 274 completed the Positive and Negative Syndrome Scale (PANSS) and Brief Negative Symptom Scale (BNSS). Information on employment status, work outcomes and demographics were collected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 70 publications
3
8
0
Order By: Relevance
“…Strauss et al ( 51 ) reported that patients with AA symptoms were less likely to be gainfully employed and less likely to complete high-quality work than patients with DE symptoms. In line with our result, Ang et al ( 56 ) showed that AA, not DE, was significantly associated with employment status, but the impact of neurocognition or functional capacity was not considered in their study.…”
Section: Discussionsupporting
confidence: 87%
“…Strauss et al ( 51 ) reported that patients with AA symptoms were less likely to be gainfully employed and less likely to complete high-quality work than patients with DE symptoms. In line with our result, Ang et al ( 56 ) showed that AA, not DE, was significantly associated with employment status, but the impact of neurocognition or functional capacity was not considered in their study.…”
Section: Discussionsupporting
confidence: 87%
“…A study of SE programs in unemployed individuals showed that the presence of a comorbid physical condition was predictive of lower rates of competitive employment, fewer hours worked, and lower wages earned over the 2-year follow-up period [ 39 ]. A negative association between somatic comorbidity and employment was also observed in other studies [ 40 , 41 ]. Other predictors are also discussed in connection with employment in patients with SMI.…”
Section: Discussionsupporting
confidence: 84%
“…This is evident in the study of Ang M (2020), which stated that people with positive symptoms had a lower chance of finding work. (67) In those who resided in city had high level of positive symptoms than the village residents. In a similar way, Padhy S (2014) The study liked urban living with psychosis because living in an urban location causes greater stress and increases the risk of psychosis.…”
Section: Discussionmentioning
confidence: 94%